Study of the genetic variability and similarity among and within Arachis villosulicarpa, A-pietrarellii and A-hypogaea through isoenzyme analysis - Galgaro, L.; Valls, JFM; Lopes, C. R. (Kluwer Academic Publ, 1997)
Arachis villosulicarpa is a perennial species cultivated for its soft and tasty seeds by indigenous inhabitants of the Mate Grosso State, Brazil. Besides A. hypogaea, this species is considered as the only species of Arachis which represents a valuable food source for human consumption. Due to the lack of knowledge concerning the genetic diversity of A. villosulicarpa, this study was conducted to evaluate the genetic variability of the accessions from the Germplasm Collection of CENARGEN/EMBRAPA (Brasilia, DF, Brazil) and Institute Agronomico (IAC, Campinas, SP, Brazil). In addition, the genetic similarity between A. villosulicarpa, the related wild species A. pietrarellii, and the cultivated peanut A. hypogaea cv. Tatu was evaluated. From the entire sample analyzed of A. villosulicarpa, the accession from Institute Agronomico showed the highest indices of diversity for both enzymatic systems analyzed, pointing this accession as a promising source of genetic variability that must be preserved in the Germplasm Bank. A high level of genetic similarity was observed between A. pietrarellii and A. villosulicarpa, supporting previous suggestions that A. pietrarellii could be the ancestral progenitor species of A. villosulicarpa or that both species originated from a common ancestor.
Keywords: Arachis; genetic similarity; genetic variability; germplasm; isoenzymes; peanuts